(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The Covid-19 pandemic has certainly had a negative impact on several business sectors in Indonesia. One of those affected was the famous tofu SMEs in Kediri. This study aims to determine the impact of the Covid-19 pandemic on Tofu SMEs in the city of Kediri, East Java, Indonesia. There are five aspects used as benchmarks in this study, including financial distress, bankruptcy, operational efficiency, and evaluation of marketing. This study measures each of these aspects whether it has an impact on the performance of tofu SMEs partially or simultaneously. The method used in this study using a questionnaire obtained a sample of 200 respondents. Then, each data from the sample was processed using multiple linear regression. The results show, partially, financial distress, operational efficiency, and evaluation of marketing have an impact on the performance of tofu SMEs in Kediri, while bankruptcy does not. However, simultaneously, these four aspects have an impact on the performance of Tofu SMEs in Kediri City. The success rate of this study was 78.5%. From the research carried out, it can be advised Tofu SMEs in Kediri to keep innovating, developing, and reducing unnecessary costs to survive the Covid-19 pandemic.